The Clinical Research Office of the Endourological Society (CROES) Multicentre Randomised Trial of Narrow Band Imaging-Assisted Transurethral Resection of Bladder Tumour (TURBT) Versus Conventional White Light Imaging-Assisted TURBT in Primary Non-Muscle-invasive Bladder Cancer Patients: Trial Protocol and 1-year Results - Naito, Seiji; Algaba, Ferran; Babjuk, Marko; Bryan, Richard T; Sun, Ying-Hao; Valiquette, Luc; de la Rosette, Jean; CROES Narrow Band Imaging Global Study Group (European urology, 2016)
BACKGROUND: White light (WL) is the established imaging modality for transurethral resection of bladder tumour (TURBT). Narrow band imaging (NBI) is a promising addition. OBJECTIVES: To compare 12-mo recurrence rates following TURBT using NBI versus WL guidance. DESIGN, SETTING, AND PARTICIPANTS: The Clinical Research Office of the Endourological Society (CROES) conducted a prospective randomised single-blind multicentre study. Patients with primary non-muscle-invasive bladder cancer (NMIBC) were randomly assigned 1:1 to TURBT guided by NBI or WL. INTERVENTION: TURBT for NMIBC using NBI or WL. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Twelve-month recurrence rates were compared by chi-square tests and survival analyses. RESULTS AND LIMITATIONS: Of the 965 patients enrolled in the study, 481 patients underwent WL-assisted TURBT and 484 patients received NBI-assisted TURBT. Of these, 294 and 303 patients, respectively, completed 12-mo follow-up, with recurrence rates of 27.1% and 25.4%, respectively (p=0.585, intention-to-treat [ITT] analysis). In patients at low risk for disease recurrence, recurrence rates at 12 mo were significantly higher in the WL group compared with the NBI group (27.3% vs 5.6%; p=0.002, ITT analysis). Although TURBT took longer on average with NBI plus WL compared with WL alone (38.1 vs 35.0min, p=0.039, ITT; 39.1 vs 35.7min, p=0.047, per protocol [PP] analysis), lesions were significantly more often visible with NBI than with WL (p=0.033). Frequency and severity of adverse events were similar in both treatment groups. Possible limitations were lack of uniformity of surgical resection, data on smoking status, central pathology review, and specific data regarding adjuvant intravesical instillation therapy. CONCLUSIONS: NBI and WL guidance achieved similar overall recurrence rates 12 mo after TURBT in patients with NMIBC. NBI-assisted TURBT significantly reduced the likelihood of disease recurrence in low-risk patients. PATIENT SUMMARY: Use of a narrow band imaging technique might provide greater detection of bladder tumours and subsequent treatment leading to reduced recurrence in low-risk patients.
Keywords: Young Adult; Male; Narrow Band Imaging; White light imaging; lokální recidiva nádoru; Transurethral resection of bladder tumour; mladý dospělý; Adolescent; nádory močového měchýře; Neoplasm Invasiveness; Adult; Aged; dospělí; Clinical Protocols; mužské pohlaví; senioři; úzkopásmové zobrazení; Prospective Studies; mladiství; světlo; Neoplasm Recurrence, Local; senioři nad 80 let; Single-Blind Method; lidé; ženské pohlaví; Humans; invazivní růst nádoru; Non–muscle-invasive bladder cancer; jednoduchá slepá metoda; Aged, 80 and over; Tumour recurrence; Urinary Bladder Neoplasms; klinické protokoly; Light; Female; lidé středního věku; Narrow band imaging; Middle Aged; prospektivní studie